Pengaruh Model Pembelajaran Kooperatif Tipe Student Teams Achievement Divisions Terhadap Hasil Belajar Matematika Siswa - Vina Hidayah Islami; Harry Soeprianto; Sudi Prayitno (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This research aims to find out the influence of the cooperative learning model of STAD type toward mathematics learning achievement of 8th grade student in SMPN 7 Mataram first semester academic year 2019/2020 on the subject matter of relations and functions. This true experiment research was designed using pretest-posttest control group design. Two classes were selected as a research subject with cluster random sampling technique, namely class VIII-B as the experimental class and VIII-C as the control class. Data collection tehniques were used observation and tests. The statistical analysis used was t-test gain and effect size to see the influence of using the STAD type cooperative learning model toward students' mathematics learning outcomes in SMPN 7 Mataram. The results showed there were differences in the improvement of mathematics learning achievement of mathematics between students who obtained learning with STAD type cooperative model and students who learned with direct learning model. The contribution of the STAD type cooperative learning model to students' mathematics learning achievement was in high category. This showed that learning using STAD type cooperative learning model had a positive influence toward mathematics learning achievement for students of grade 8th in SMPN 7 Mataram.